Left Ventricular Hypertrophy: Major Risk Factor in Patients with Hypertension: Update and Practical Clinical Applications - Richard E. Katholi; Daniel M. Couri (International Journal of Hypertension)
Left ventricular hypertrophy is a maladaptive response to chronic pressure overload and an important risk factor for atrial fibrillation, diastolic heart failure, systolic heart failure, and sudden death in patients with hypertension. Since not all patients with hypertension develop left ventricular hypertrophy, there are clinical findings that should be kept in mind that may alert the physician to the presence of left ventricular hypertrophy so a more definitive evaluation can be performed using an echocardiogram or cardiovascular magnetic resonance. Controlling arterial pressure, sodium restriction, and weight loss independently facilitate the regression of left ventricular hypertrophy. Choice of antihypertensive agents may be important when treating a patient with hypertensive left ventricular hypertrophy. Angiotensin-converting enzyme inhibitors or angiotensin II receptor blockers followed by calcium channel antagonists most rapidly facilitate the regression of left ventricular hypertrophy. With the regression of left ventricular hypertrophy, diastolic function and coronary flow reserve usually improve, and cardiovascular risk decreases.